2005
DOI: 10.3133/sir20045146
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characteristics of ground-water discharge along the south rim of Grand Canyon in Grand Canyon National Park, Arizona, 2000-2001

Abstract: Map showing surficial geology, geologic structure, and chemical characteristics of ground-water discharge at selected springs and creeks along the south rim

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 17 publications
3
41
0
Order By: Relevance
“…However, also possible is a proto-Grand Canyon river that could have supplied higher strontium-ratio carbonate to the Claron Formation in its southeastern part (where we sampled). If the higher strontium values of Redwall aquifer water are mixed with Kaibab Limestone values (∼ 0.709; Monroe et al, 2005), then the intermediate 87 Sr/ 86 Sr values measured for the Claron may reflect a contribution of a proto-Grand Canyon drainage system into the Claron basin.…”
Section: Lake Claronmentioning
confidence: 93%
“…However, also possible is a proto-Grand Canyon river that could have supplied higher strontium-ratio carbonate to the Claron Formation in its southeastern part (where we sampled). If the higher strontium values of Redwall aquifer water are mixed with Kaibab Limestone values (∼ 0.709; Monroe et al, 2005), then the intermediate 87 Sr/ 86 Sr values measured for the Claron may reflect a contribution of a proto-Grand Canyon drainage system into the Claron basin.…”
Section: Lake Claronmentioning
confidence: 93%
“…Few springs in the eastern GC basin are warmer than 19°C, primarily because the region's highelevation plateaus provide cool groundwater recharge, and many groundwater flowpaths there are relatively short (Monroe et al 2005); however, Monroe et al (2005) reported several warmwater springs emanating from the South Rim of GC with groundwater residence times exceeding 3000 years. Most GC springs emerge either as contact-hanging-gardens springs (vertical habitats that support few ASH taxa) or in structurally controlled channels that are regularly scoured by floods (Springer et al 2006).…”
Section: Ecotonesmentioning
confidence: 97%
“…The Big Springs and Muav Faults displace the Fig. 6 Strontium isotope ratio relative to 1/strontium concentration for spring samples; values from rock samples in Bills et al 2007 andMonroe et al 2005 uplifted area of the Kaibab Plateau from the western portion of our study area including Snake Gulch. Several springs discharge along the Big Springs Fault (Warm, Oak, Tilton, Mangum and Big springs); however, there is no perennial surface water flowing away from these springs, which indicates that the water discharging at the springs may then reinfiltrate into the subsurface.…”
Section: Groundwater Flowpaths and Residence Timesmentioning
confidence: 99%